2012
DOI: 10.1186/1472-684x-11-24
|View full text |Cite
|
Sign up to set email alerts
|

Older patients’ attitudes towards and experiences of patient-physician end-of-life communication: a secondary analysis of interviews from British, Dutch and Belgian patients

Abstract: BackgroundOlder patients often experience sub-standard communication in the palliative phase of illness. Due to the importance of good communication in patient-centred end-of-life care, it is essential to understand the factors which influence older patients’ communication with physicians. This study examines older patients’ attitudes towards, and experiences of, patient-physician end-of-life (EoL) communication in three European countries.MethodsA secondary analysis of interviews from British, Dutch and Belgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 29 publications
2
33
0
2
Order By: Relevance
“…[26][27][28][29] Rodriguez and Young 24 also found that service users questioned the benefit of lifesustaining interventions in situations where they perceived their quality of life as unacceptable. As in MND, people with advanced cancer prefer to be in control over treatment decisions and end-of-life care.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[26][27][28][29] Rodriguez and Young 24 also found that service users questioned the benefit of lifesustaining interventions in situations where they perceived their quality of life as unacceptable. As in MND, people with advanced cancer prefer to be in control over treatment decisions and end-of-life care.…”
Section: Discussionmentioning
confidence: 93%
“…Empathy and genuine concern from healthcare professionals can engender trust in the service user, but a lack of sensitivity on behalf of service providers can diminish service users' trust in service providers. 27 Our findings shed light on MND service users' perceptions of life-sustaining treatments and of palliative care. We found that participants were resigned to death because of the terminal nature of MND, and they were averse to the notion of prolonging life in MND for the sake of longevity alone.…”
Section: Discussionmentioning
confidence: 94%
“…Internationally and nationally, there is a recent intensive debate on health care needs in older age, as well as emerging efforts to facilitate primary palliative care to alleviate the end of life of patients with non-malignant life limiting illness or advanced frailty [5,17,32,40,41]. In this study, the health care related needs and experiences of frail elderly patients as well as their informal caregivers and family physicians will be analysed.…”
Section: Discussionmentioning
confidence: 99%
“…Several, repeated interviews within an 18 months period may be a barrier for some patients. However, published experiences [32,40,41] demonstrate that patients can, and indeed appreciate to talk about personal and sensitive issues such as increasing functional decline, death, dying, and bereavement in repeated interviews over a longer period of time. We expect a 30% drop out due to withdrawal or non-ability to be interviewed any more, and 30% due to death.…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, the literature indicates that quality shared decision-making occurs only about 10% of the time, 6,15 adoption in practice has been slow 9 and there is a lack of evidence about how to successfully implement shared decision-making. 16 Shared decision-making is essential in palliative care in order to elicit preferences about care, including place of care; however, recent research indicates mixed implementation, [17][18][19] which may be due to particular difficulty of using shared decision-making in integrated care sites such as palliative care, where decisions need to be negotiated between, and shared with, multiple health and social care practitioners, employed carers, patients and their family carers. 20 It is important that patient preferences are discussed in advance of end-of-life care, before lack of capacity sets in, to avoid unwanted, futile, aggressive and costly medical treatment, avoid the cessation of treatment when continuation is preferred and to ensure that preferred place of care or death is clear to all.…”
Section: Introductionmentioning
confidence: 99%